The Role of University-based Business Incubation and Innovation Hubs in Accelerating Student Entrepreneurial Learning - Muazu, Muazu Hassan; Bello, Shukurat M. (Majalah Ilmiah Bijak, 2025)
This research investigates the role of university business incubation and innovation hubs in student entrepreneurial learning. Universities worldwide have increasingly established incubation centres and innovation hubs to foster student entrepreneurship. However, despite these initiatives, their effectiveness in facilitating entrepreneurial learning remains largely unexplored. The objective of this study is to bridge this gap by examining the impact of university incubation and innovation hubs on the development of student entrepreneurs. The study used a case-study research approach, and gather comprehensive data from students of Bayero University, Kano, who have undergone the incubation program within the university. The data was collected through a closed-ended questionnaire on students' experiences with university-based entrepreneurship support programs, including seminar, business ideas competition, hackathon, business plan competition, coaching/mentorships, and study tour/industry. The Statistical Package for Social Science (SPSS) is the tool used for the data analysis and presentation. Analysis techniques such as descriptive statistics, correlation and regression analysis are conducted, and the result indicated significant effect of the programs of the university innovation and incubation hubs on students venture start-up, except for seminar. About 30 students’ businesses were registered to fruition in 2022-2023 and millions of naira were won as grants by students from different donors. Furthermore, the study identifies key challenges encountered by students in leveraging these initiatives and propose strategies for enhancing their effectiveness. The implications of the findings derived from this research are manifold. The results provide valuable insights for university administrators, policymakers, and educators seeking to optimize entrepreneurship education programs within their institutions